Preface: Focus Meeting 10 - Stellar explosions in an ever-changing environment. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Thöne, Christina C.; Christensen, Lise; ,
Abstract : This focus meeting builds on a small conference "Galaxies meet GRBs at Cabo de Gata" held in September 2013 in Spain, which, for the first time, brought together people from the GRB and starburst communities and proved to be a great success. Focus Meeting 10 at the XXIX IAU GA was the continuation of this interdisciplinary collaboration, supported by Division J (Galaxies and Cosmology), Division D (High Energy Phenomena and Fundamental Physics) and Division G Working Group "Massive Stars".